How people with knee pain understand why their pain changes or remains the same over time: A qualitative study - David A. Walsh; James Rathbone; Kehinde Akin-Akinyosoye; Gwen S. Fernandes; Ana M. Valdes; Daniel F. McWilliams; Weiya Zhang; Michael Doherty; Jennie E. Hancox; Kavita Vedhara; Roshan das Nair; Eamonn Ferguson (Osteoarthritis and Cartilage Open, 2023)
Objectives: Guidelines recommend knee osteoarthritis pain management based on biopsychosocial mechanisms. Treatment adherence and effectiveness may be affected if there is a mismatch between patient perspectives and treatment focus. We therefore examined patient perspectives on mechanisms of their knee pain, why it persisted or changed over the past year, whether their understanding had changed, and whether their understanding aligned with that of others with whom they interact. Methods: Individuals with chronic knee pain (n ​= ​50) were purposively recruited from the Knee Pain and related health In the Community (KPIC) cohort to represent worsened, improved, or unchanged pain or anxiety between baseline and one year later. Framework analysis, a comparative form of thematic analysis, was used across transcripts of semi-structured telephone interviews. Results: Data were collapsed into themes of diagnosis, joint structure, ageing, physical activity, weight management, and treatment. Participants focused on biomechanical rather than psychological pain mechanisms. Some participants attributed pain improvement to increased and others to decreased physical activity. Participants reported no change in their understanding of their pain during the preceding year, but that their attitudes to pain, for example acceptance, had changed. Participants reported that they and others around them lacked understanding of their pain and why it did or did not change. Conclusion: People report a predominantly biomechanical understanding of why their knee pain remains constant or changes over time. Clinicians should support patients to develop a biopsychosocial understanding of knee pain aligned to treatment across the range of biological, psychological, and social modalities.